Analysis of the Stability of Nalut Formation Outcrops Parallel to Al-Rujban Mountain Road-NW Libya - Reda Almagtuf; Aboalgasem Alakhdar (AlQalam Journal of Medical and Applied Sciences, 2025)
The slopes parallel to mountain roads are affected by both natural and human factors, such as slope-cutting processes during road construction, making slope stability assessment essential. Factors like rainfall and improper rock-cutting angles contribute to slope weakness and rockfalls, causing road damage and posing risks to users. This study aims to assess the stability of the Nalut Formation outcrops along the Al-Rujban mountain road. A field study was conducted, where the site was coded (L-R-R-21), and two locations (L1, L2) were selected to collect samples and measure fractures and joints, as well as study rock mass properties, including the Rock Quality Designation index. Results showed that site L1 contains three joint systems (S1, S2, S3), where S1 and S2 intersect at a 90° angle, reducing the RQD value to 44%, classifying it as "poor." The joint system indicated a wide spacing between rock masses, with an average joint spacing (JS) of 89 cm, categorizing it as widely spaced. Slope cutting at 90° led to rockfalls. The lower rock formations were smaller due to random fractures, while the upper formations were larger and more hazardous when collapsing. The study recommends removing fallen blocks and regularly monitoring the slopes to ensure user safety. تتأثر المنحدرات الموازية للطرق الجبلية بالعوامل الطبيعية والبشرية كعمليات قطع المنحدرات أثناء إنشاء الطرق، مما يجعل تقييم استقرار المنحدرات أمرًا ضروريًا، تساهم عوامل مثل هطول الأمطار والزوايا غير المناسبة لقطع الصخور في حدوث ضعف المنحدرات وحدوث الانهيارات الصخرية، مما يسبب أضرارًا للطرق ويشكل خطرًا على مستخدميها. يهدف هذا البحث إلى تقييم استقرار مكاشف تكوين نالوت على طول للطريق الجبلي الرجبان؛ تم إجراء دراسة ميدانية، حيث تم ترميز الموقع بـ (L-R-R-21) واختيار موقعين (L1- L2) بهدف جمع العينات وإجراء القياسات المتعلقة بالشقوق والفواصل ودراسة خصائص الكتل الصخرية، بما في ذلك مؤشر متانة الصخور(RQD)؛ أظهرت النتائج أن الموقع L1 يحتوي على ثلاثة أنظمة للفواصل الصخرية S1)، S2، S3 (حيث تتقاطع الفواصل S1 و S2 بزاوية 90°، مما أدى إلى انخفاض قيمة RQD إلى 44%، وصُنّفت على أنها "ضعيفة". كما أشار نظام الفواصل إلى وجود تباعد كبير بين الكتل الصخرية، حيث تم قياس متوسط المسافة بين الفواصل (JS) بـ 89 سم، مما يصنّفها ضمن الفواصل المتباعدة بشكل كبير. وأدى قطع المنحدرات بزاوية 90° إلى حدوث انهيارات صخرية. أما الصخور في الجزء السفلي من التكوين فكانت أصغر حجمًا بسبب كثرة التشققات العشوائية، في حين كانت الصخور في الجزء العلوي من التكوين أكبر حجمًا وأكثر خطورة في حال انهيارها، وتوصي الدراسة بإزالة الكتل الصخرية المنهارة نظرًا لخطرها، ومراقبة الطريق ومنحدراته بشكل دوري للكشف عن أي تغيرات قد تؤثر على استقراره، مما يساهم في ضمان استدامة الطريق وسلامة مستخدميه